Nearby Low-Mass Hypervelocity Stars. Issue 67 (17th July 2015) - Zhang, Y.Q.; Smith, M.C.; Carlin, J.L.
Abstract : Hypervelocity stars are those that have speeds exceeding the escape speed and are hence unbound from the Milky Way. We investigate a sample of low-mass hypervelocity candidates obtained using data from the high-precision SDSS Stripe 82 catalogue, which we have combined with spectroscopy from the 200-inch Hale Telescope at Palomar Observatory. We find four good candidates, but without metallicities it is difficult to pin-down their distances and therefore total velocities. Our best candidate has a significant likelihood that it is escaping the Milky Way for a wide-range of metallicities.